Thermodynamic Kinetic Parameters of Some Transition Metal Complexes of Schiff Base - Mane, P.S.; Salunke, S.D.; Shirodkar, S.G.; Chondhekar, T.K. (Asian Journal of Chemistry, 2010)
Complexes of Cu(II), Ni(II), Co(II), Fe(IlI) and Mn(II) with Schiff base are prepared by condensation of 3-acety-6-methyl-(2H}-pyran- 2,4(3H)dione (dihydroacetic acid) with o-toluidine. The ligand acts as bidentate molecule. The kinetic parameters for their decomposition have been evaluated by Coats-Redfern method from TG data. The values of kinetic and thermodynamic parameters are comparable and the decomposition follows a reaction mode.